A method for preparing photocatalysts with carbon atom clusters directionally modified on TiO2(001) surfaces

CN118079889BActive Publication Date: 2026-10-20DONGGUAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410214927.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2026-10-20
Estimated Expiration
2044-02-27

AI Technical Summary

Technical Problem

[0004]针对现有技术存在的上述不足,本发明的目的在于提供一种碳原子团簇定向修饰TiO2(001)表面的光催化剂制备方法,以解决现有光催化技术中催化剂的本征催化活性和光吸收能力差的问题

Benefits of technology

[0018]1、本发明采用以碳布作为衬底材料,成功制备了以主要暴露(001)高活性表面的TiO2纳米片,并利用碳原子团簇定向修饰了TiO2的(001)表面,从而形成了碳原子团簇改性后的TiO2@碳布的复合材料,通过暴露活性面和采用碳原子团簇修饰的策略,显著提高了该材料的光催化活性和光吸收能力及载流子的分离效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118079889B_ABST
    Figure CN118079889B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a photocatalyst for directional modification of a TiO2 (001) surface by a carbon atom cluster, and specifically comprises the following steps: step 1, slowly adding tetrabutyl titanate into a dilute hydrochloric acid solution, uniformly stirring, quickly adding an HF solution and uniformly stirring to obtain a mixed solution; wherein, the concentration of the dilute hydrochloric acid solution is 5-20% according to mass percentage; and the molar ratio of tetrabutyl titanate, HCl and HF is (1.5-4):10:(0.1-7); step 2, adding carbon cloth into a reaction kettle and also adding the mixed solution obtained in step 1 into the reaction kettle, and reacting at 120-200 DEG C for 2-12 hours; step 3, cleaning and drying the reaction product obtained in step 2 to obtain a composite material TiO2@CC; and step 4, annealing the composite material obtained in step 3 at 200-500 DEG C for 1-6 hours to obtain the photocatalyst C-TiO2@CC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalyst technology, specifically to a method for preparing a photocatalyst by directional modification of TiO2(001) surface with carbon atom clusters. Background Technology

[0002] Environmental pollution is one of the major challenges facing the world today. With the rapid development of industry and urbanization, problems such as air pollution, water pollution, and soil pollution are becoming increasingly prominent. For example, emissions of nitrogen oxides (NOx), which cause air pollution, often contain various toxic and harmful components, severely impacting not only the ecological environment but also the normal lives of residents in surrounding areas. Therefore, promoting and achieving efficient treatment of various pollution sources is of paramount practical significance. Photocatalysis technology utilizes the absorption of light by a catalyst to form photogenerated charge carriers, thereby promoting redox reactions and achieving pollutant removal. This technology boasts advantages such as sustainability, eco-friendliness, and low cost, and is considered one of the green, economical, and efficient new technologies for treating toxic and harmful pollutants. However, the core of photocatalysis technology lies in the design and preparation of photocatalyst materials. Currently, there are many types of photocatalyst materials attracting attention, such as titanium dioxide, zinc oxide, bismuth oxide, and graphitic C3N4 semiconductors.

[0003] Titanium dioxide (TiO2) has become a photocatalytic material with great development potential due to its environmental friendliness, excellent thermal stability, low cost, and suitable band gap. Furthermore, TiO2 has three different crystal phases: anatase, rutile, and azurite. Previous studies have shown that the anatase phase has the best photocatalytic activity. However, the wide band gap (3.2 eV) of the anatase phase TiO2 severely restricts its light absorption performance, allowing it to absorb only ultraviolet light and not responding to visible light. This results in a low yield of photogenerated carriers and a high recombination rate, significantly affecting its photocatalytic activity. In addition, the crystal faces of the anatase phase TiO2 often have different surface energies and surface catalytic activities. The average surface energies of the (100), (101), and (001) surfaces are 0.53, 0.44, and 0.90 J / m², respectively. -2Furthermore, the adsorption and photocatalytic oxidation capabilities of the (001) surface, which possesses higher surface energy, are far superior to those of other surfaces. This is due to the high surface energy and the advantage of five coordinated Ti atoms on the (001) surface, which are conducive to redox reactions. Therefore, preparing TiO2 catalysts with exposed highly active (001) surfaces, and employing strategies such as surface modification and heterojunction construction, can effectively enhance the light absorption performance of anatase TiO2 and suppress carrier recombination, thereby improving photocatalytic activity. However, due to the high surface energy of the (001) crystal facet of anatase TiO2, Ti and O atoms tend to accumulate in large quantities on the (001) crystal facet during crystal growth, and then grow along a direction perpendicular to the crystal facet. This results in the (001) crystal facet of anatase TiO2 being completely covered and difficult to expose, thus affecting the catalytic effect of the catalyst. Summary of the Invention

[0004] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a method for preparing photocatalysts by directional modification of TiO2(001) surfaces with carbon atom clusters, thereby solving the problems of poor intrinsic catalytic activity and light absorption capacity of catalysts in existing photocatalytic technologies.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] A method for preparing a photocatalyst with carbon atom clusters directionally modified on the surface of TiO2(001) specifically includes the following steps:

[0007] Step 1: Slowly add tetrabutyl titanate to dilute hydrochloric acid solution, stir until homogeneous, then quickly add HF solution and stir until homogeneous to obtain a mixed solution; wherein, according to the mass percentage, the concentration of dilute hydrochloric acid solution is 5% to 20%; and the molar ratio of tetrabutyl titanate, HCl and HF is (1.5 to 4): 10: (0.1 to 7).

[0008] Step 2: Add carbon cloth to the reactor and also add the mixed solution obtained in Step 1 to the reactor, and react at 120-200℃ for 2-12 hours;

[0009] Step 3: After washing and drying the reaction product obtained in Step 2, the composite material TiO2@CC is obtained;

[0010] Step 4: Anneal the composite material obtained in Step 3 at 200-500℃ for 1-6 hours to obtain the photocatalyst C-TiO2@CC.

[0011] Preferably, in step 2, the carbon cloth is treated with dilute nitric acid solution as follows:

[0012] The carbon cloth was ultrasonically washed 2-3 times in a dilute nitric acid solution, with each ultrasonic washing lasting 0.5 hours. After each ultrasonic washing, the carbon cloth was rinsed with water several times before the next ultrasonic washing. Finally, the carbon cloth was dried. The concentration of the dilute nitric acid solution was 5% by mass percentage.

[0013] Preferably, in step 3, the product after the reaction in step 2 is washed with a sodium hydroxide solution, the concentration of which is 0.01–0.1 mol / L.

[0014] Preferably, in step 2, the reaction temperature is 140–180°C.

[0015] This invention provides a photocatalyst application for the directional modification of TiO2(001) surface with carbon atom clusters, wherein the photocatalyst catalyzes the degradation of methylene blue under visible light.

[0016] This invention provides a photocatalyst application for the directional modification of TiO2(001) surface with carbon atom clusters, wherein the photocatalyst catalyzes the oxidation and removal of NO under visible light.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. This invention uses carbon cloth as a substrate material to successfully prepare TiO2 nanosheets with the (001) highly active surface mainly exposed. The (001) surface of TiO2 is then directionally modified with carbon atom clusters to form a composite material of TiO2@carbon cloth modified with carbon atom clusters. By exposing the active surface and using the strategy of modifying with carbon atom clusters, the photocatalytic activity, light absorption capacity and carrier separation efficiency of the material are significantly improved.

[0019] 2. The catalyst prepared by the method described in this invention exhibits excellent photocatalytic performance under full-spectrum conditions in the degradation of organic dyes and removal of air pollutants, taking the degradation of methylene blue and removal of nitric oxide as examples. It also highlights photocatalytic activity under visible light conditions and the good stability of the catalytic material. Attached Figure Description

[0020] Figure 1 (a) XRD patterns of TiO2@CC and C-TiO2@CC; Figure 1 (b) shows the photocurrent response curves of TiO2@CC and C-TiO2@CC under visible light conditions.

[0021] Figure 2 (a) and (b) are SEM images of TiO2@CC at different magnification sizes, respectively; Figure 2(c) and (d) are SEM images of C-TiO2@CC at different magnification sizes, respectively.

[0022] Figure 3 (a) and (b) are the HRTEM spectra of TiO2@CC, respectively; Figure 3 (c) and (d) are the HRTEM spectra of C-TiO2@CC, respectively.

[0023] Figure 4 In the image: (a) Degradation performance of TiO2@CC and C-TiO2@CC on methylene blue under visible light conditions; (b) Spectral absorption diagram of the degradation process of methylene blue by C-TiO2@CC under visible light conditions; (c) Degradation performance of C-TiO2@CC on methylene blue under different light conditions; (d) Degradation stability of C-TiO2@CC on methylene blue under visible light conditions.

[0024] Figure 5 In the middle: (a) shows the oxidative removal performance of NO by TiO2@CC and C-TiO2@CC under visible light conditions; (b) shows the stability of NO oxidative removal by C-TiO2@CC under visible light conditions.

[0025] Figure 6 In the middle: under visible light conditions, the degradation performance of C-TiO2@CC (Comparative Example 2) and C-TiO2@CC (Example 1) on methylene blue. Detailed Implementation

[0026] The technical solutions of the present invention will be clearly and completely described in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the present invention are within the scope of protection of the present invention.

[0027] Unless otherwise specified in the specific circumstances, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within that range, but are not limited to the specific values ​​listed when the range is defined.

[0028] I. A method for preparing a photocatalyst with carbon atom clusters directionally modified on the surface of TiO2(001).

[0029] Step 1: Slowly add tetrabutyl titanate to dilute hydrochloric acid solution, stir until homogeneous, then quickly add HF solution and stir until homogeneous to obtain a mixed solution; wherein, according to the mass percentage, the concentration of dilute hydrochloric acid solution is 5% to 20%; and the molar ratio of tetrabutyl titanate, HCl and HF is (1.5 to 4): 10: (0.1 to 7).

[0030] Step 2: Add carbon cloth to the reactor and also add the mixed solution obtained in Step 1 to the reactor, and react at 120-200℃ for 2-12 hours;

[0031] Step 3: After washing and drying the reaction product obtained in Step 2, the composite material TiO2@CC is obtained;

[0032] Step 4: Anneal the composite material obtained in Step 3 at 200-500℃ for 1-6 hours to obtain the photocatalyst C-TiO2@CC.

[0033] This invention conducts an in-depth study on the preparation of TiO2 catalysts. To prepare TiO2 catalysts with exposed highly active (001) surfaces, it is necessary to reduce the surface energy of this crystal plane and limit the crystal growth rate along the perpendicular (001) surface. Theoretical calculations show that F ions can effectively reduce the surface energy of the (001) crystal plane. Therefore, introducing F ions during the preparation of TiO2 catalysts helps to expose the (001) crystal plane. However, although this method helps to expose the (001) crystal plane, the prepared catalysts often suffer from poor morphological uniformity and a low proportion of exposed (001) crystal planes. In addition, although the strategy of exposing highly active surfaces helps to improve the intrinsic catalytic activity of photocatalysts, the TiO2 catalysts prepared under this strategy still have poor light absorption capacity, especially the disadvantage of no response in the visible light range. This is also a major factor restricting the development of efficient TiO2 catalysts. Therefore, this invention, while reducing the surface energy of the (001) crystal plane, needs to consider ensuring that the (001) surface of the catalyst is exposed and has a high exposure ratio. This invention introduces sufficient F ions during the preparation process to ensure full exposure of the (001) crystal plane, and uses carbon fiber material as a substrate to promote the formation of a catalyst with good uniformity of microstructure. Simultaneously, it cleans the catalyst surface with sodium hydroxide solution to prevent excessive adsorption of F ions, thereby reducing the number of surface active sites. Furthermore, to improve the light absorption capacity of the TiO2 catalyst, a simple heat treatment method is used to induce the directional formation of carbon atom clusters on the (001) surface of the TiO2 catalyst, resulting in a catalyst with excellent catalytic performance, C-TiO2@CC.

[0034] In some implementations, the ratio of tetrabutyl titanate, HCl, and HF is important, and it is necessary to ensure that there is sufficient F in the reaction system. - F in the reaction system - If the amount is too low, it will not be conducive to the exposure of the (001) crystal plane, resulting in a small exposure area of ​​the (001) crystal plane, which will be difficult to play a role in improving the catalytic effect; while F -If the amount of HCl is too high, it will lead to poor catalyst morphology uniformity. Therefore, the molar ratio of tetrabutyl titanate, HCl, and HF needs to be controlled within the range of (1.5–4):10:(0.1–7), for example, 1.5:10:0.1, 4:10:7, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the embodiments, any of the above ranges can be combined with any other range.

[0035] In some embodiments, in step 2, the present invention screens the substrate material of the catalyst and finds that using other fiber materials can easily lead to the catalyst failing to form a uniform microstructure. Therefore, carbon cloth fiber is used as the substrate to ensure that the obtained catalyst has good uniformity. However, the carbon cloth fiber material needs to be pretreated. The carbon cloth is treated with dilute nitric acid solution. The purpose of treating the carbon cloth with dilute nitric acid is to acidify the surface of the carbon cloth fiber material and remove some impurities on the surface of the carbon cloth, such as oily hydrophobic substances, some metal atoms, etc. If other dilute acids, such as dilute hydrochloric acid, are used, the carbon cloth surface may not be cleaned thoroughly. The specific steps of treating the carbon cloth with dilute nitric acid are as follows: the carbon cloth is immersed in dilute nitric acid solution and ultrasonically washed 2-3 times, with each ultrasonic washing lasting 0.5 hours. After each ultrasonic washing, the carbon cloth is rinsed with water multiple times before the next ultrasonic washing. Finally, the carbon cloth is dried. The concentration of the dilute nitric acid solution is 5% by mass percentage.

[0036] In some embodiments, the purpose of washing the synthesized sample with sodium hydroxide solution in step 3 is to eliminate residual F ions on the surface of the synthesized catalyst, reduce the occupation of active sites by F ions, and ensure sufficient exposure of active sites on the catalyst surface. Therefore, using too low a concentration of sodium hydroxide may make it difficult to completely remove the adsorbed F ions from the catalyst surface, while using too high a concentration of sodium hydroxide will leave some sodium hydroxide residue on the catalyst surface, leading to an increase in the number of times the reaction products are washed, which in turn occupies the active sites on the catalyst surface, resulting in insufficient active sites and thus a decrease in the photocatalytic performance of the catalyst. The product after the reaction in step 2 is washed with sodium hydroxide solution at a concentration of 0.01–0.1 mol / L. Washing the product after the reaction in step 2 with sodium hydroxide solution can significantly improve the photocatalytic performance of the prepared catalyst, especially compared with catalysts obtained without washing or with other solutions (such as water or alcohol solutions), the improvement in photocatalytic performance is very significant. Therefore, the concentration of the sodium hydroxide solution can be 0.01 mol / L, 0.05 mol / L, 0.06 mol / L, 0.08 mol / L, 0.1 mol / L, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0037] In some embodiments, in step 2, the reaction temperature is further controlled within the range of 140–180°C. Too low a reaction temperature will prevent the proper preparation of the TiO2 catalyst, while too high a reaction temperature will result in a large TiO2 catalyst size, even exceeding the defined size of nanomaterials. Furthermore, the TiO2 catalyst will become crowded on the carbon fiber, reducing morphological uniformity. Therefore, the reaction temperature is further optimized to be between 140 and 180°C, which can be 140°C, 150°C, 160°C, 170°C, 180°C, etc., as well as all ranges and sub-ranges between these values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0038] In some embodiments, the annealing temperature in step 4 is controlled between 200 and 500°C. If the annealing temperature is too low, carbon atom clusters cannot form on the (001) surface of the TiO2 catalyst; if the annealing temperature is too high, carbon atoms will accumulate in large quantities on the (001) surface of the TiO2 catalyst and completely cover the active surface of the catalyst. Therefore, the annealing temperature can be 200°C, 250°C, 350°C, 450°C, etc., and all ranges and sub-ranges between these values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0039] II. Application of a photocatalyst with carbon atom clusters directionally modified on TiO2(001) surface

[0040] The photocatalyst catalyzes the degradation of methylene blue under visible light.

[0041] III. Application of a photocatalyst with carbon atom clusters directionally modified on TiO2(001) surface

[0042] The photocatalyst catalyzes the oxidation and removal of NO under visible light.

[0043] IV. Examples and Comparative Examples

[0044] Example 1

[0045] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0046] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth treated with dilute nitric acid solution to the reactor lining. Specifically, place the purchased commercial carbon cloth in a 5% (w / w) dilute nitric acid solution and ultrasonically wash it 2-3 times, each time for 0.5 hours. Then, wash the carbon cloth treated with dilute nitric acid multiple times with pure water. Finally, place the carbon cloth in a 60°C oven to dry, and then carry out a hydrothermal reaction at 140°C for 2 hours.

[0047] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0048] Step 4: The obtained composite material is annealed at 250℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0049] Example 2: Effect of F ion concentration ratio on morphology and structure

[0050] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.5 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0051] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 140°C for 2 hours.

[0052] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0053] Step 4: The obtained composite material is annealed at 250℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0054] Example 3: Effect of hydrothermal reaction temperature

[0055] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0056] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 180°C for 2 hours.

[0057] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0058] Step 4: The obtained composite material is annealed at 250℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0059] Example 4: Effect of heat treatment temperature

[0060] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0061] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 140°C for 2 hours.

[0062] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0063] Step 4: The obtained composite material is annealed at 350℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0064] Example 5: Effect of heat treatment temperature

[0065] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0066] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 140°C for 2 hours.

[0067] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0068] Step 4: The obtained composite material is annealed at 450℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0069] Comparative Example 1: Without heat treatment, directional modification of carbon atom clusters cannot be achieved.

[0070] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0071] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 140°C for 2 hours.

[0072] Step 3: The product after the reaction in Step 2 is first washed with a 0.05 mol / L NaOH solution, then washed with water and ethanol, and dried at 60°C to obtain a TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0073] Comparative Example 2: Failure to wash the reaction products with NaOH solution will significantly reduce photocatalytic performance.

[0074] Step 1: Prepare a 10% hydrochloric acid solution. Take 30 mL of the dilute hydrochloric acid solution in a beaker and stir continuously with a magnetic stirrer. At the same time, slowly add 0.5 mL of tetrabutyl titanate to the dilute hydrochloric acid solution. After stirring for 0.5 h, take 0.1 mL of 20% HF solution and quickly inject it into the mixed solution. Continue stirring for another 0.5 h.

[0075] Step 2: Transfer the mixed solution obtained in Step 1 to a Teflon hydrothermal reactor, and add a piece of carbon cloth that has been ultrasonically treated with dilute nitric acid solution to the reactor lining. Then carry out the hydrothermal reaction at 140°C for 2 hours.

[0076] Step 3: Wash the product after the reaction in Step 2 with water and ethanol, and dry it at 60°C to obtain the TiO2@carbon cloth composite material (TiO2@CC) with the (001) highly active surface exposed.

[0077] Step 4: The obtained composite material is annealed at 250℃ for 1 hour to obtain a composite photocatalytic material (C-TiO2@CC) with carbon atom clusters oriented to modify the TiO2(001) surface.

[0078] V. Performance Analysis

[0079] Figure 1 (a) shows the XRD patterns of TiO2@CC (Comparative Example 1) and C-TiO2@CC (Example 1), which reflect the crystal structure of the composite material prepared in the examples, wherein TiO2 is the anatase phase, and carbon cloth and carbon atom clusters are amorphous phases; Figure 1 (b) shows the photocurrent response curves of TiO2@CC and C-TiO2@CC under visible light conditions, indicating that the TiO2@CC prepared in the examples constitutes a heterojunction and has a weak response under visible light conditions, while the directional modification of carbon atom clusters contributes to the photocurrent response under visible light. Other examples are the same as in Example 1, exhibiting the same photocurrent response.

[0080] Figure 2 (a) and (b) are SEM images of TiO2@CC (Comparative Example 1) at different magnification sizes. Figure 2 (c) and (d) are SEM images of C-TiO2@CC (Example 1) at different magnifications, reflecting the morphology and structure of the composite material prepared in the examples, wherein TiO2 is a two-dimensional nanosheet structure that is uniformly and densely grown on carbon cloth fibers. Meanwhile, the same morphology and structure as in Example 1 can be observed in other examples.

[0081] Figure 3 (a) and (b) are the HRTEM spectra of TiO2@CC (Comparative Example 1). Figure 3 (c) and (d) are HRTEM images of C-TiO2@CC (Example 1), which show that the main exposed surface of the anatase phase TiO2 is the highly active (001) surface, confirming that carbon atom clusters are successfully anchored on the (001) surface of the composite material. Other examples are the same as in Example 1, which also confirms that carbon atom clusters are anchored on the (001) surface of the composite material.

[0082] Figure 4 (a) Degradation performance of TiO2@CC (Comparative Example 1) and C-TiO2@CC (Example 1) on methylene blue under visible light conditions; (b) Spectral absorption diagram of the degradation process of methylene blue by C-TiO2@CC under visible light conditions; (c) Degradation performance of C-TiO2@CC on methylene blue under different illumination conditions; (d) Degradation stability of C-TiO2@CC on methylene blue under visible light conditions. The prepared sample material was used as a photocatalyst filter (27 cm² area). 2 Under the illumination of a 350W xenon lamp, 100ml of 2×10 -5 A mol / L methylene blue solution was slowly filtered through a catalyst filter. One cycle consisted of 100 ml of solution being completely filtered. The spectral absorbance of methylene blue after each filtration was measured using a spectrophotometer, and the degradation performance was evaluated using the absorbance at a wavelength of 654 nm. Simultaneously, the illumination conditions were adjusted by controlling the xenon lamp filter. Under visible light conditions, after five filtrations, C-TiO2@CC completely degraded methylene blue with an adsorption efficiency of 65%. In contrast, the TiO2@CC catalyst showed a degradation efficiency of less than 10% and an adsorption efficiency of only 20%, indicating that exposing a highly active surface is beneficial for improving the catalyst's pollutant removal performance. Furthermore, comparisons of the catalytic performance of C-TiO2@CC under full-spectrum and visible light irradiation showed that carbon atom clusters can effectively enhance light absorption. Moreover, even with multiple changes of the methylene blue solution while maintaining the same catalyst, the C-TiO2@CC catalyst still exhibited excellent photocatalytic performance, indicating good catalyst stability.

[0083] Figure 5(a) Oxidative removal performance of NO by TiO2@CC (Comparative Example 1) and C-TiO2@CC (Example 1) under visible light conditions; (b) Stability of NO oxidative removal by C-TiO2@CC under visible light conditions. NO with a concentration of 600 ppb was selected as the degradation target, with an area of ​​27 cm². 2 Using the sample material as a photocatalyst, the performance and stability of the synthesized sample for NO oxidation and removal were evaluated under irradiation with a 350W xenon lamp with ultraviolet light filtered out. C-TiO2@CC achieved a NO removal efficiency of 55%, while TiO2@CC's efficiency was less than 15%. Furthermore, C-TiO2@CC exhibited good stability in repeated tests, retaining excellent catalytic performance even after multiple uses.

[0084] Figure 6 Under visible light conditions, the degradation performance of C-TiO2@CC (Comparative Example 2) and C-TiO2@CC (Example 1) on methylene blue, i.e. the effect of washing the reaction products with sodium hydroxide and without sodium hydroxide on the catalytic performance, showed that the degradation performance and adsorption performance of the reaction products washed with sodium hydroxide solution were about 15% to 20% higher than those washed with sodium hydroxide solution.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a photocatalyst with carbon atom clusters directionally modified on the surface of TiO2(001), characterized in that, Specifically, the steps include the following: Step 1: Slowly add tetrabutyl titanate to dilute hydrochloric acid solution, stir until homogeneous, then quickly add HF solution and stir until homogeneous to obtain a mixed solution; wherein, according to the mass percentage, the concentration of dilute hydrochloric acid solution is 5%~20%; and the molar ratio of tetrabutyl titanate, HCl and HF is (1.5~4):10:(0.1~7). Step 2: Add carbon cloth to the reactor, and also add the mixed solution obtained in Step 1 to the reactor. React at 120~200℃ for 2~12 hours. In Step 2, before adding the carbon cloth to the reactor, it is first treated with dilute nitric acid solution, specifically as follows: The carbon cloth was ultrasonically washed 2-3 times in a dilute nitric acid solution, with each ultrasonic washing lasting 0.5 hours. After each ultrasonic washing, the carbon cloth was rinsed several times with water before the next ultrasonic washing. Finally, the carbon cloth was dried. The concentration of the dilute nitric acid solution was 5% by mass. Step 3: After washing and drying the reaction product obtained in Step 2, the composite material TiO2@CC is obtained; the product after the reaction in Step 2 is washed with sodium hydroxide solution with a concentration of 0.01~0.1mol / L. Step 4: Anneal the composite material obtained in Step 3 at 200~500℃ for 1~6h to obtain the photocatalyst C-TiO2@CC.

2. The method for preparing a photocatalyst with carbon atom clusters directionally modified on the surface of TiO2(001) according to claim 1, characterized in that, In step 2, the reaction temperature is 140~180℃.

3. An application of a photocatalyst for the directional modification of TiO2(001) surfaces with carbon atom clusters, characterized in that, The photocatalyst prepared by the preparation method according to claim 1 or 2 can catalyze the degradation of methylene blue under visible light and the oxidative removal of NO under visible light.

Citation Information

Patent Citations

  • Method for loading titania microflowers on shaped carbon material

    CN107573102A

  • Method for preparing carbon-modified titania film

    TW201326047A